Information and Emotional Support Needs of Families Whose Infant Was Diagnosed With SCID Through Newborn Screening - Raspa, Melissa; Lynch, Molly; Squiers, Linda; Gwaltney, Angela; Porter, Katherine; Peay, Holly; Huston, Alissa; Fitzek, Brian; Boyle, John G. (Frontiers in Immunology, 2020)
Background: Now that severe combined immunodeficiency (SCID) has been added to newborn screening panels in all 50 states in the U.S., there is a need to develop and disseminate well-designed educational materials to parents who need information to make informed decisions about treatment and care for identified infants. SCID Compass was designed to address this gap. We summarize the results of two needs assessment activities for parents – a journey mapping exercise and online survey—which will inform the development of a website and new resources. Methods: We conducted in-depth interviews with seven parents of children with SCID identified through newborn screening. Participants were asked to complete a journey map to describe key timepoints related to SCID, starting at diagnosis through present day. This qualitative information informed an online survey that was completed by 76 parents who had a child with SCID. All participants were from the United States. Results: Analysis of journey maps revealed five distinct stages that parents experience: (1) Diagnosis, (2) Pre-Treatment, (3) Treatment, (4) Post-Treatment, and (5) The New Normal. At each stage, parents described unique emotions, challenges, contextual factors that can make a difference in their experience, and information and resource needs. Survey results indicated the highest-rated information needs for parents were understanding available treatment options and what to expect across the SCID lifespan. Emotional support needs included dealing with uncertainty about child’s future and additional opportunities to connect with other families. Parents preferred receiving new materials from their healthcare provider or other families, and preferred materials in print, from social media, or online. Several differences were found among subgroups of parents, including those whose child had been identified through newborn screening as well as those considered medically underserved. Conclusions: Findings about unmet parent needs and informational preferences will serve as the foundation for creating a suite of resources for those who have a child with SCID. The materials will be tailored to specific stages of the journey. By using a family-centered approach, we will help to ensure that the materials designed and developed as part of SCID Compass will be understandable, comprehensive, and useful.